2015
DOI: 10.1002/lsm.22361
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of different modes of fractional CO2 laser in the treatment of primary cutaneous amyloidosis: A randomized clinical trial

Abstract: Background Primary cutaneous amyloidosis (PCA) comprises three main forms: macular, lichen, and nodular amyloidosis. The current available treatments are quite disappointing. Objectives Assess and compare the clinical and histological changes induced by different modes of Fractional CO2 laser in treatment of PCA. Patients and Methods Twenty five patients with PCA (16 macular and 9 lichen amyloidosis) were treated by fractional CO2 using; superficial ablation (area A) and deep rejuvenation (area B). Each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…15 Esmat et al, when compared efficacy of different modes of fractional carbon dioxide laser in treatment of primary cutaneous amyloidosis, demonstrated that both superficial and deep mode showed comparable efficacy whereas superficial mode is better tolerated by patients. 16…”
Section: Discussionmentioning
confidence: 99%
“…15 Esmat et al, when compared efficacy of different modes of fractional carbon dioxide laser in treatment of primary cutaneous amyloidosis, demonstrated that both superficial and deep mode showed comparable efficacy whereas superficial mode is better tolerated by patients. 16…”
Section: Discussionmentioning
confidence: 99%
“…A case report of PDL treatment in a 57-year-old man with recalcitrant macular amyloidosis who was treated with three sessions of PDL at 2-week intervals showed improvement after each treatment ( Barsky and Buka, 2014 ). This resulted from a decrease in collagen and dermatan sulfate synthesis that is similar to the mechanism behind the reduction of the size of hypertrophic scars ( Esmat et al, 2015 ). The QS-Nd:YAG laser has also been studied in 20 patients with clinically diagnosed and pathologically confirmed macular amyloidosis who were treated with both 532 nm and 1064 nm doses in different parts or plaques.…”
Section: Notalgia Paresthetica and Macular Amyloidosismentioning
confidence: 95%
“…Few studies have looked at the treatment of macular amyloidosis by laser therapy. One study of 25 patients with primary cutaneous amyloidosis used both superficial ablation and deep rejuvenation with a fractional CO 2 laser and found a significant reduction in pigmentation, thickness, itching, and amyloid deposition ( Esmat et al, 2015 ). In this study, superficial ablation was preferred by patients due to decreased pain with comparable efficacy ( Stellon, 2002 ).…”
Section: Notalgia Paresthetica and Macular Amyloidosismentioning
confidence: 99%
“…Topical dimethyl sulfoxide 50% solution in water was found to be beneficial in some cases with rapid and marked improvement of papules and itch (9), whereas partial and transient reduction of pruritus but no amyloid-dissolving properties have been reported by others (24). Fractional CO2 laser has been used to treat 25 patients affected by PCA with some benefit, using both superficial and deep modes of fractional laser (25). Two patients affected by lichen amyloidosis have been treated with CO2 surgical laser with good response especially for the pruritus, after a failed treatment with topical corticosteroids in both cases (26).…”
Section: Case Reportmentioning
confidence: 99%